HIV as Chronic Illness: Caregiving and Social Networks in a Vulnerable Population. (May 2015) - Mignone, Javier; Migliardi, Paula; Harvey, Carol; Davis, Jennifer; Madariaga‐Vignudo, Lucia; Pindera, Carla
Abstract : N/A: We sought to understand the support networks of people living with HIV (PLWH) in the Canadian cities of Winnipeg and Regina, particularly of their network of caregivers and with a focus on people from disadvantaged and/or stigmatized communities. Using a variation of the Photovoice method, 31 study participants took photographs of their everyday realities and were then interviewed. Among the findings was the heavy reliance on institutional caregivers and on nonhuman sources of support. There was evidence of peer‐to‐peer networks of care, but the strongest connections were with their formal caregivers. HIV as a chronic condition among disadvantaged and/or stigmatized groups requires paying special attention to informal and formal care dynamics and to where social or family networks cannot meet the basic needs. Honing in on and enhancing these features through programs and services can only improve the situation of stigmatized yet hopeful and resilient PLWH.